2010
DOI: 10.1007/s00192-010-1179-0
|View full text |Cite
|
Sign up to set email alerts
|

Validity of the Rome III Criteria in assessing constipation in women

Abstract: The Rome III Criteria questionnaire is a reliable and reproducible tool but does not appear to be a valid instrument in diagnosing constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 25 publications
0
18
1
1
Order By: Relevance
“…Since different time periods are being rated (subjects began keeping the diary after giving their retrospective rating of the past year), perfect agreement would not be expected. Digesu and colleagues [9] utilizing respondents from urogynecology, gynecology, and colorectal clinics found that women had difficulty recalling bowel symptoms that had occurred even within a 6-month period. With recall there is the potential for recall bias to influence responses to bowel questionnaires [1719].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since different time periods are being rated (subjects began keeping the diary after giving their retrospective rating of the past year), perfect agreement would not be expected. Digesu and colleagues [9] utilizing respondents from urogynecology, gynecology, and colorectal clinics found that women had difficulty recalling bowel symptoms that had occurred even within a 6-month period. With recall there is the potential for recall bias to influence responses to bowel questionnaires [1719].…”
Section: Discussionmentioning
confidence: 99%
“…But this information may not capture the typical bowel pattern. For example, in one study investigators noted that women with functional constipation had difficulty remembering if symptoms had occurred more or less during a 6-month period [9]. Daily pain and stooling recorded over 4 weeks may provide different information than retrospective recall over several months.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 For constipation to be defined as chronic, a patient must be symptomatic for at least 6 months with applicable criteria for the previous 3 months. 3,9 Although the validity of the Rome III criteria for constipation has been recently questioned, 10 with a known disparity between self-reported and criteria-based definitions, 11 the use of colonic transit time 12,13 and anorectal function tests 14 as diagnostic tools is still controversial. In general, the prevalence of constipation among the general population in North America has been quoted as 1.9% to 27.2%, 15,16 with 50% to 74% of the institutionalized elderly reporting daily use of laxatives.…”
mentioning
confidence: 99%
“…One goal was to aid in pathophysiological understanding, diagnosis, and medical treatment through the evaluation of the constipation sufferer's condition (Agachan, Chen, Pfeifer, Reissman, & Wexner, 1996;Knowles et al, 2000 ;Varma et al, 2008 ). Another study sought to compare the Rome international criteria with the sufferer's self-reported awareness of constipation ( Digesu et al, 2010 ;Garrigues et al, 2004 ). The aim in another study was simply to diagnose functional constipation and assess its symptoms ( Chan et al, 2005 ).…”
Section: The Outline and Features Of The Assessment Scalesmentioning
confidence: 99%